Profit planning decisions with the break-even system - Tucker, Spencer A. (New York, N.Y. : Thomond Press, 1980)
This book gives simple tools for obtaining picture of the profit structure so that the best possible decisions can be made on current questions involving: pricing, product mix selection, territorial profitability, end market profitability, salesperson, justification of expenditures etc.
Includes index.
osa 29/01/2019
Loans
Keywords: Break-even analysis; Profit